An improved VOF method with anti-ventilation techniques for the hydrodynamic assessment of planing hulls-Part 2: Applications. (1st October 2021) - Cui, Lianzheng; Chen, Zuogang; Feng, Yukun; Li, Guibin; Liu, Jianguo
Abstract: The improved volume of fluid (VOF) method proposed in Part 1 to eliminate the numerical ventilation (NV) was applied to predict the hydrodynamic characteristics of an experimentally studied planing hull. The simulated ship motions were the trim and sinkage. The overset mesh method was employed to avoid undesirable mesh deformation. The results of the improved and conventional VOF methods were reported and compared with the experimental data. The captured wetted surface and spray phenomenon, which were prone to the NV, were visualized to manifest the advantage of the improved method in capturing them. The flow field of the spray area (SA), which has been rarely numerically studied due to the NV, was also investigated to provide a reference for quantifying the spray friction resistance and evaluate some related formulae. The comparison demonstrated a considerable accuracy improvement of the improved VOF method. The visualization also showed a significant elimination effect on the NV. The study on the SA indicated that the spray thickness might limit the boundary layer thickness, leading to a low Reynolds number. Furthermore, the spray thickness and the velocity of the area were not constant, which induced the relatively large gradient of the wall shear stress magnitude. Highlights: The improved volume of fluid (VOF) method proposed in Part 1 was applied and validated. The results of the improved and conventional VOF methods were compared. The wetted surface area and spray phenomenon were visualized. The flow field of the spray area was investigated numerically. Several formulae related to the spray area were evaluated.